The natural history of anal transition zone inflammation and possible relationship to pouchitis: a long‐term longitudinal study. (December 2013) - Wasserman, M.; Hyman, N.; Iyer, A.; Wilcox, R.; Osler, T.
Abstract Aim Reservoir ileitis (pouchitis) is the most common complication after pelvic pouch surgery for ulcerative colitis and the aetiology remains largely unknown. The anal transition zone (ATZ) contains the only remaining colonic epithelium after ileal pouch anal anastomosis (IPAA) and may provide important clues as to whether ulcerative colitis and pouchitis share a common pathogenesis. The aim of this study was to evaluate longitudinally the long‐term histological changes in the ATZ and their relationship to the incidence of pouchitis. Method Patients with a double‐stapled IPAA for ulcerative colitis at an academic medical centre with at least 10 years of clinical and histological follow‐up were identified from a prospective database. Annual ATZ and pouch biopsies were taken and interpreted by two expert gastrointestinal pathologists. ATZ histological variability score, the incidence of pouchitis, and function were correlated over time. ATZ biopsies were scored from one to three based on the extent of inflammation. Results Sixteen of the 114 patients having IPAA fulfilled the criteria for admission to the study. There were 179 biopsies of the ATZ. All exhibited variability in ATZ histology over time and 81% had a 2‐unit change in their inflammatory score. There was no correlation between pouchitis and histological severity score of the ATZ. Similarly, function over time did not vary with the intensity of ATZ inflammation. Conclusion ATZ inflammation varies substantially over time in most patients. But these changes from year to year did not correlate with function or the occurrence of pouchitis.